1984
DOI: 10.1136/bmj.288.6435.1950
|View full text |Cite
|
Sign up to set email alerts
|

Release of beta endorphin and met-enkephalin during exercise in normal women: response to training.

Abstract: Plasma 0 endorphin and met-enkephalin concentrations were measured in response to treadmill exercises in 15 normal women before, during, and after an intensive programme of exercise training. Significant release of J endorphin occurred in all three test runs, and the pattern and amount of release were not altered by training. Before training dramatic release of met-enkephalin was observed in seven subjects and smaller rises observed in a further four, and this response was almost abolished by training. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(63 citation statements)
references
References 25 publications
1
60
1
1
Order By: Relevance
“…The post-exercise plasma concentractions of P-endorphin observed in this study were higher than previous values reported for similar exercise intensities in thermoneutral conditions [4,9,12,15]. The added thermal stress may have partially augmented the magnitude of the plasma concentrations observed.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The post-exercise plasma concentractions of P-endorphin observed in this study were higher than previous values reported for similar exercise intensities in thermoneutral conditions [4,9,12,15]. The added thermal stress may have partially augmented the magnitude of the plasma concentrations observed.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, exercise previously has been demonstrated to increase various EOP levels such as Methionine-enkephalin (Metenkephalin), Peptide F and -endorphin [4,5,9,11,12,15,19]. It has been suggested that training may also effect exercise responses of f-endorphin and Peptide F 3 --61 [4,19].…”
mentioning
confidence: 99%
“…When elevated in the bloodstream, endorphins produce an opiate-like state that has mild analgesic effects [63]. Research indicates that endorphins are particularly responsive to low-level muscular pain [64] and psychological or emotional distress [65]. As Dunbar suggested, endorphins project to areas of the brain well positioned to receive input from physical touch, yet direct evidence linking endorphin levels to touch in humans is lacking because endorphins can be sampled only in cerebrospinal fluid, making them difficult to assay [50].…”
Section: Potential Mechanisms Linking Pain and Touchmentioning
confidence: 99%
“…Physical exercise is known to stimulate the release of endogenous opioids (endorphins) (Howlett et al 1984;Seeger et al 1984;Harbach et al 2000;Madsen et al 2007;Boecker et al 2008). Psychologically, endorphin release is experienced as a mild opiate 'high', a corresponding feeling of well-being, and light analgesia (Belluzi & Stein 1977;Stephano et al 2000), reflecting the role that endorphins play as part of the pain control system.…”
Section: Introductionmentioning
confidence: 99%